Cuticular hydrocarbons corroborate the distinction between lowland and highland Natal fruit fly (Tephritidae, Ceratitis rosa) populations - Vaníčková, Lucie; Břízová, Radka; Pompeiano, Antonio; Ekesi, Sunday; Meyer, Marc De (ZooKeys, 2015)
The cuticular hydrocarbons (CHs) and morphology of two Ceratitis rosa Karsch (Diptera: Tephritidae) populations, putatively belonging to two cryptic taxa, were analysed. The chemical profiles were characterised by two-dimensional gas chromatography with mass spectrometric detection. CHs of Ceratitis rosa that originated from the lowlands and highlands of Kenya comprised of n-alkanes, monomethylalkanes, dimethylalkanes and unsaturated hydrocarbons in the range of the carbon backbone from C14 to C37. Hydrocarbons containing C29, C31, C33 and C35 carbon atoms predominated in these two populations. 2-Methyltriacontane was the predominant compound in both populations. Quantitative differences in the distribution of hydrocarbons of different chain lengths, mainly the C22, C32, C33 and C34 compounds of these two populations, were observed despite indistinct qualitative differences in these hydrocarbons. Morphological analyses of male legs confirmed that the flies belong to different morphotypes of Ceratitis rosa previously labelled as R1 and R2 for lowland and highland populations, respectively. A statistical analysis of the CH compositions of the putative R1 and R2 species showed distinct interspecific identities, with several CHs specific for each of the lowland and highland populations. This study supports a hypothesis that the taxon Ceratitis rosa consists of at least two biological species.
Keywords: cryptic species; integrative taxonomy; chemotaxonomy; Ceratitis rosa; GC×GC/MS